Mesenteric Meckel's diverticulum in a 17 month old female - Paige Koetter; Eric Cochran; Anthony Y. Tsai (Elsevier, 2021)
Meckel's diverticulum is a common gastrointestinal anomaly that is a remnant of the omphalomesenteric duct which typically remains on the antimesenteric border of the small intestine. Mesenteric variation of the Meckel's diverticulum are uncommon and only 22 cases have been reported in the literature. We report a case of a 17 month old female presenting with a symptomatic lower gastrointestinal bleed and an ambiguous mesenteric lesion on ultrasound subsequently found to be a mesenteric Meckel's diverticulum. The existing literature was reviewed to understand age and presentation of mesenteric Meckel's diverticulum cases. We also review the differential, including presentation and epidemiology for mesenteric lesions in children.